2016
DOI: 10.3389/fpls.2016.01305
|View full text |Cite
|
Sign up to set email alerts
|

An ATL78-Like RING-H2 Finger Protein Confers Abiotic Stress Tolerance through Interacting with RAV2 and CSN5B in Tomato

Abstract: RING finger proteins play an important role in plant adaptation to abiotic stresses. In the present study, a wild tomato (Solanum habrochaites) cold-induced RING-H2 finger gene, ShATL78L, was isolated, which has been identified as an abiotic stress responsive gene in tomato. The results showed that ShATL78L was constitutively expressed in various tissues such as root, leaf, petiole, stem, flower, and fruit. Cold stress up-regulated ShATL78L in the cold-tolerant S. habrochaites compared to the susceptible culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…It is also possible that other zinc-finger proteins use a similar mechanism to promote abiotic stress tolerance. For instance, recent research from our colleague revealed that an ATL78-like RING-H2-finger protein (ShATL78L) can interact with CSN5B in tomato and that overexpressing this protein can enhance the tolerance of tomato to multiple abiotic stresses (Song et al, 2016).…”
Section: Zinc-finger Protein Functions As a New Regulator For Ascorbamentioning
confidence: 99%
“…It is also possible that other zinc-finger proteins use a similar mechanism to promote abiotic stress tolerance. For instance, recent research from our colleague revealed that an ATL78-like RING-H2-finger protein (ShATL78L) can interact with CSN5B in tomato and that overexpressing this protein can enhance the tolerance of tomato to multiple abiotic stresses (Song et al, 2016).…”
Section: Zinc-finger Protein Functions As a New Regulator For Ascorbamentioning
confidence: 99%
“…Actually, LOC107817253 and LOC107782318 are both RING‐H2 finger protein ATL2‐like, which has been reported to be associated with plant resistance in tomato ( Lycopersicon esculentum Mill.) (Song et al., 2016) and rice (Park, Choi, Kim, & Jang, 2019). Therefore, we speculated that LOC107815159 might respond to low NO 3 − stress by regulating the expression of RING‐H2 finger protein.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expressions of a number of genes involved in the synthesis of these protective compounds have been found to be changed (Table 5). For example, the RING finger protein, besides the role as a ROS scavenger, was found to be also involved in the synthesis of proline, soluble carbohydrate, and osmotic regulation [48][49][50]. In the transgenic Arabidopsis plants with higher expression of the RING finger gene, the proline and sugar contents were increased and this…”
Section: Compatible Compounds Synthesis and Osmotic Regulationmentioning
confidence: 99%